Advancing therapeutic strategies for graft-versus-host disease by targeting gut microbiome dynamics in allogeneic hematopoietic stem cell transplantation: current evidence and future directions - Muhammad Azhar Ud Din; Yan Lin; Changkun Lyu; Chengxue Yi; Anning Fang; Fei Mao (Molecular Medicine)
Abstract Hematopoietic stem cell transplantation (HSCT) is a highly effective therapy for malignant blood illnesses that pose a high risk, as well as diseases that are at risk due to other variables, such as genetics. However, the prevalence of graft-versus-host disease (GVHD) has impeded its widespread use. Ensuring the stability of microbial varieties and associated metabolites is crucial for supporting metabolic processes, preventing pathogen intrusion, and modulating the immune system. Consequently, it significantly affects the overall well-being and susceptibility of the host to disease. Patients undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT) may experience a disruption in the balance between the immune system and gut bacteria when treated with medicines and foreign cells. This can lead to secondary intestinal inflammation and GVHD. Thus, GM is both a reliable indicator of post-transplant mortality and a means of enhancing GVHD prevention and treatment after allo-HSCT. This can be achieved through various strategies, including nutritional support, probiotics, selective use of antibiotics, and fecal microbiota transplantation (FMT) to target gut microbes. This review examines research advancements and the practical use of intestinal bacteria in GVHD following allo-HSCT. These findings may offer novel insights into the prevention and treatment of GVHD after allo-HSCT.